INNOVATIVE APPROACHES TO RESEARCH SKILL DEVELOPMENT FRAMEWORKS FOR EVALUATING PROBLEM-SOLVING SKILLS IN DESIGN PROJECTS IN INDONESIAN HIGHER EDUCATION - Khaerudin; Yudi Hendrilia; Ratna Ayu Pawestri Kusuma Dewi; Erwin; Al-Amin (Indonesian Journal of Education (INJOE), 2023)
This study explored innovative approaches to research skill development frameworks for evaluating problem-solving skills in design projects within the context of Indonesian higher education. The research focused on enhancing problem-solving skills, which are crucial for success in design-related fields, by incorporating elements of design thinking principles and John Willison's Research Skill Development (RSD) framework. The study employed a mixed- methods research design, combining qualitative and quantitative methods to assess the innovative frameworks' effectiveness comprehensively. Through developing and integrating these frameworks into design project courses, students were guided through problem identification, research methodologies, data collection, and solution prototyping. Faculty members played a facilitating role in this process. The comparative analysis between the innovative frameworks and traditional assessment methods revealed that the former significantly outperformed the latter. Students engaged with the frameworks exhibited enhanced creativity, adaptability, and metacognitive reflection in their problem-solving approaches. They demonstrated growth in problem identification, research strategies, and critical evaluation of information sources. This study has significant implications for Indonesian higher education, emphasizing the advantages of innovative assessment methods in design education. The research skill development frameworks offer a dynamic and holistic approach to problem-solving skill development, preparing graduates to excel in the competitive and evolving design industry. However, challenges related to adaptation and resource allocation were acknowledged. Ultimately, this research underscores the transformative potential of research skill development frameworks in enhancing problem-solving skills, bridging the gap between theory and practice, and preparing graduates to shape future design in Indonesia